Inhibition of antigen-specific T lymphocyte activation by structurally related Ir gene-controlled polymers. Evidence of specific competition for accessory cell antigen presentation (The Rockefeller University Press, 1983)
The interaction of nominal Ag with major histocompatibility complex (MHC)-restricted T cells and accessory cells was studied by analyzing the effect of structurally related antigens on the response of antigen- specific MHC-restricted T cell hybridomas. The copolymer L-glutamic acid50-L-tyrosine50 (GT) completely inhibits the response of L-glutamic acid60-L-alanine40-L-tyrosine10 (GAT)-specific, I-Ad-restricted T cell hybridomas to GAT plus accessory cells. This inhibition is specific, as hybridomas of other specificities are not inhibited under identical conditions, and is unique to the GT antigen, as other similar copolymers are not inhibitory. The inhibitory effect is reversible by adding increasing amounts of GAT. Antigen-pulsing experiments localized the inhibition to the level of antigen-presenting cell (APC). GT- prepulsed APC are not inhibitory in cell-mixing experiments and can present other antigens. GT only inhibits the nominal antigen-directed component of a GAT-specific, autoreactive hybrid's response. Together these findings suggest that GT causes inhibition by competing for GAT association at the accessory cell. GT interferes with GAT presentation by an I-Adxb F1 APC to a BALB/c, I-Ad-restricted, but not B10, I-Ab- restricted, T cell hybridoma, and GT inhibits presentation by GAT- prepulsed APC. The implications of these findings for MHC-restricted presentation of antigen are discussed.